Electrically Tunable Transparent Displays for Visible Light Based on Dielectric Metasurfaces - Zou, Chengjun; Komar, Andrei; Fasold, Stefan; Bohn, Justus; Muravsky, Alexander A.; Murauski, Anatoli A.; Pertsch, Thomas; Neshev, Dragomir N.; Staude, Isabelle (ACS Photonics, 2019)
Tunable dielectric metasurfaces able to manipulate visible light with high efficiency are promising for applications in displays, reconfigurable optical components, beam steering, and spatial light modulation. Infiltration of dielectric metasurfaces with nematic liquid crystals (LCs) is an attractive tuning approach, which is highly compatible with existing industrial platforms for optical and electronic devices. Here, we demonstrate electrically tunable transparent displays based on nematic LC-infiltrated tunable dielectric metasurfaces at visible frequencies. Importantly, the technique of photoalignment of LCs is adopted to improve the LC prealignment quality and thus the tuning accuracy and contrast in the visible. By applying a voltage across the infiltrated metasurface cell, we observe resonance shifts that are more than twice larger than their line width. We track the spectral shifts of the electric and magnetic dipole resonances as they move into and out of the so-called Huygens' regime of high transparency originating from spectrally overlapping electric and magnetic dipole resonances. Furthermore, we realize a switchable metasurface display with a measured modulation depth of 53% at 669 nm operation wavelength for an applied voltage of 20 V. The novel LC tuning platform demonstrated in our work may lead to the development of next-generation LC display devices that are able to overcome current limitations of minimal pixel size and speed of operation.
CRIS-Team Scopus Importer:2023-04-20
Keywords: all-dielectric nanophotonics; displays; liquid crystals; metadevices; Mie resonances; tunable metasurfaces